FORMAÇÃO E IDENTIDADE DE PROFESSORES DE EDUCAÇÃO FÍSICA NAS “ESCOLAS DAS ÁGUAS” DO PANTANAL SUL-MATO-GROSSENSE - ANDREZA SUMÁRA GOMES DOS SANTOS (2022)
The Water Schools of the southern Mato Grosso Pantanal, when compared to the schools located in the city, are considered atypical with regard to social, cultural, economic and natural issues. The routine of these schools is influenced by the water cycle of the Pantanal plain. Among their limitations, most of them are the lack of resources and precarious facilities, in addition to the teaching challenges for the teachers who accept to work in these schools. Therefore, some questions arise regarding the performance of Physical Education teachers who work and have worked in the Water Schools: What are the teaching challenges that influence the construction of the identity of these teachers? Do Physical Education teachers understand the relationship between teaching identity and initial training? In order to answer these questions, this research aims to understand the identity with a focus on the training of Physical Education teachers who work or have worked in the Water Schools in the Pantanal of southern Mato Grosso. The specific objectives are: (i) to analyze the narrative of Physical Education teachers about the concept of identity developed in their initial training; (ii) to write and interpret how the teaching challenges of the Water Schools of the South Pantanal of Mato Grosso influence the identity of the Physical Education teacher; (iii) to verify the contribution of the initial training process in the construction of the physical education teacher's identity in the Water Schools of the South Pantanal of Mato Grosso. The research is qualitative, descriptive and exploratory. To collect data, it was used a narrative interview, with a semi-structured script, carried out with teachers who worked or work in the Water Schools of the Southern Pantanal of Mato Grosso. The data obtained were organized, categorized and analyzed according to Szymanski's proposal (2011). With analysis of the data obtained, it is clear that the initial and continuing education of teachers needs to happen differently, specifically focused on the reality of riverside communities, considering the cultural and social aspects in the learning process, requiring a timely and incisive intervention, when it comes to the preparation of these professionals. Parallel to this situation, Physical Education teachers understand the importance of the subject for the integral formation of the riverside children, however, it is something challenging. When it comes to identity, it is noted that the experiences acquired in this context influence the construction and (re)construction of the subject's identity. Therefore, it is necessary to create continuing education courses that are increasingly specific to the public in question, as a way to provide the teacher with appropriate tools to contribute to their teaching.